Colliding Epidemics: Research Gaps and Implementation Science Opportunities for Tobacco Use and HIV/AIDS in Low- and Middle-Income Countries. (17th June 2022) - Parascandola, Mark; Neta, Gila; Bloch, Michele; Gopal, Satish
Abstract : Introduction . Tobacco use is a leading cause of cancer death among people living with HIV (PLWH) worldwide, and smoking prevalence tends to be higher among PLWH. The burden of both HIV/AIDS and tobacco use is increasingly concentrated in low- and middle-income countries (LMICs), where resources to address these challenges are often limited. However, there has been limited effort to date to integrate tobacco cessation into HIV programs in LMICs. Methods . We searched the literature (searching was conducted between October 1 and December 31, 2020) using PubMed including search terms "tobacco" and "HIV" and "cessation" over the past ten years (searching for articles published between December 1, 2010, and December 1, 2020) to identify original research studies on tobacco cessation interventions conducted in LMICs for PLWH. We also conducted an analysis of NCI-funded research grants on tobacco cessation and HIV awarded during fiscal years 2010 to 2020. Results and Discussion . Existing evidence suggests that conventional tobacco cessation treatments may be less effective among PLWH. Moreover, while substantial evidence exists to support a range of cessation interventions, most of this evidence comes from HICs and is only partly applicable to the evolving social, economic, and cultural climate of many LMICs. There is an urgent need to develop, adapt, and implement effective tobacco control and cessation interventions targeted to PLWH in LMICs, as well as to generate evidence from these settings. Implementation science provides tools develop and test strategies to overcome barriers and to integrate and scale up cessation services within existing HIV treatment settings. Conclusion . There is a unique opportunity to address HIV and tobacco use in a coordinated way in LMICs by integrating evidence-based tobacco cessation into HIV programs.